2017
DOI: 10.31235/osf.io/p2w5c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Old One-Two: Preserving Analytical Dualism in Psychological Sociology

Abstract: We argue that an important item on the agenda for the ongoing dialogue between cognitive scientists and microsociologists is how to replace Cartesian mind-body dualism. Although we agree that strict mind-body dualism should be laid to rest, we believe that replacing this dichotomy with a holistic theory risks making it harder for researchers to see analytic distinctions that make a real difference. We use examples from Loic Wacquant's Body and Soul to illustrate our argument that sociologists should replace th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In this article, we have shown that creativity emerges through a range of cognitive and bodily processes, combining conceptual and bodily knowledge as well as heuristic and analytic cognition. These findings entail an important corrective to sociological and social psychological accounts of creativity and more broadly, to sociological theories of cognition and action (e.g., Csikszentmihalyi 1996; Dewey [1922] 2002; Lizardo et al 2016; Sawyer 2006; Vaisey 2009; Vaisey and Frye forthcoming).…”
Section: The Mind and Body In Creativitymentioning
confidence: 90%
See 2 more Smart Citations
“…In this article, we have shown that creativity emerges through a range of cognitive and bodily processes, combining conceptual and bodily knowledge as well as heuristic and analytic cognition. These findings entail an important corrective to sociological and social psychological accounts of creativity and more broadly, to sociological theories of cognition and action (e.g., Csikszentmihalyi 1996; Dewey [1922] 2002; Lizardo et al 2016; Sawyer 2006; Vaisey 2009; Vaisey and Frye forthcoming).…”
Section: The Mind and Body In Creativitymentioning
confidence: 90%
“…Cultural and cognitive sociology, we have shown, have posed important challenges to dualistic ways of understanding creativity as well as cognition more generally (e.g., McDonnell 2014; Moore 2017; Vila-Henninger 2015). In response to such challenges, proponents of the sociological dual process model have argued for the value of the analytical separation between Type 1 and Type 2 processes as a productive respecification of the dualism of mind and body (Vaisey and Frye forthcoming). They argue that while mind-body holism (e.g., Ignatow 2007; Wacquant 2004) may be correct ontologically, it is analytically fruitful to treat some kinds of knowledge and action as more or less embodied and habitual than others.…”
Section: Creativity and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sociologists, following Bourdieu's () work in Distinction , have shown time and again that people's tastes for many activities and approaches to many kinds of institutions are structured by social position (e.g., Bryson ; Dimaggio and Useem ; Lareau ; Lizardo ; Vaisey ). Habitus—the set of dispositions and ways of seeing the world that is shaped by social position and trajectory (Bourdieu )—is a good way of thinking about the relationship between class and all kinds of social judgments and decisions (see Cerulo ; Lizardo ; Vaisey and Frye ); this applies just as much to politics as to art museum attendance, musical tastes, or relationships to schooling. Bourdieu (:409) described the sense that one is both a legitimate and a skilled producer of political opinions as a key component of “political competence”:
To understand the relationship between educational capital and the propensity to answer political questions, it is not sufficient to consider the capacity to understand, reproduce, and even produce political discourse, which is guaranteed by educational qualifications; one also has to consider the (socially authorized and encouraged) sense of being entitled to be concerned with politics, authorized to talk politics… .
…”
Section: Class and Relation To Politicsmentioning
confidence: 99%
“…Originally introduced to sociology in Stephen Vaisey's (2009) seminal article, the dual process model of cognition commonly adopted by cultural analysts in sociology is based on an analytical dualism that distinguishes between faster automatic and slower deliberative cognitive processes (Lizardo et al 2016; Miles 2015; Vaisey 2009; Vaisey and Frye 2019). While there is a plurality of dual process models that are moderately different when applied to distinct domains of research (such as learning, remembering, thinking, and acting), the general dual process framework subsumes distinct dual process models in each domain by distinguishing between two types of cognitive processes for different explanatory purposes (Lizardo et al 2016).…”
Section: Part 2: the Study Of Cognition In The Sociology Of Culturementioning
confidence: 99%